HIPERAKTIVITAS SARAF SIMPATIS PADA IBU HAMIL TERHADAP DINAMIKA TEKANAN DARAH - Meli Doloksaribu (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Pregnancy is something that every married couple has been waiting for. But not all pregnancies can run smoothly. There are several complications that occur during pregnancies so that it can threaten the life of the mother and fetus. One complication that often occurs is hypertension in pregnancy. This disease cause high mortality and morbidity, so it is a health problem in the community. Blood pressure is one of the hemodynamic parameters that is simple and easy to measure, blood pressure describes the hemodynamic situation of a person at that time. The autonomic nervous system causes vasoconstriction and vasodilation in maintaining blood pressure. The purpose of this study was to determine whether hyperactivity of sympathetic nerves in pregnant women has a relationship to the dynamics of blood pressure. The design of this study is a Cohort Prospective. The population is all pregnant women who visit Antenatal Care at the Jumpandang Baru Health Center in Makassar City. The sampling technique used consecutive sampling with a sample size of 40 pregnant women. Sympathetic nerve hyperactivity was evaluated by conducting a Cold Pressor Test (CPT) and blood pressure dynamics were performed by measuring blood pressure using mercury spigmomanometers and stetescopes. The test used is mann whitney. The results showed that there was no significant difference between the average systole blood pressure p: 0.732 and diastole p: 0.628. It was concluded that blood pressure is not always influenced by hyperactivity of sympathetic nerves. There are other factors that can affect a blood pressure in pregnant women. It is recommended to all pregnant women who carry out antenatal care to measure blood pressure routinely, health workers can arrange a homevisit schedule for pregnant women and provide counseling to mothers about the dangers during pregnancy so that early detection can be possible of the possibility of hypertension during pregnancy.